If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -8 = 5(x + 1) Reorder the terms: -8 + y = 5(x + 1) Reorder the terms: -8 + y = 5(1 + x) -8 + y = (1 * 5 + x * 5) -8 + y = (5 + 5x) Solving -8 + y = 5 + 5x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + y = 5 + 8 + 5x Combine like terms: -8 + 8 = 0 0 + y = 5 + 8 + 5x y = 5 + 8 + 5x Combine like terms: 5 + 8 = 13 y = 13 + 5x Simplifying y = 13 + 5x
| -1.2=2.8-2y | | 2a^2+3a-4ab-6a^2+2a-4ab+4a^2-9a+ab= | | 0.6=-3.6+4.2 | | -7y+8y+7=-9+4 | | -6(x-5)=-6x+13 | | 5a(3-b)=15a-5ab | | 3(b-3)-4=4b-28 | | -8m-8=100 | | 9x/8=10 | | 5(-1)+2y=5 | | 28-5x=4x+10 | | -7y+8y+7=-6+5 | | 6x+9=2x+41 | | -98=-2p-7(p+5) | | 2x+1.5=7.3 | | 70000=2002.3x-3964125 | | -6x-15=4x+25 | | 70000=2002.3-3964125 | | 2x-3(0)=10 | | 4r-9=2r+1 | | 4x+3y+z=-6 | | 0=5x^2-34x-48 | | 5p-(3+2p)=12 | | 2(3y+5)-3y=10 | | -9m-11=109 | | E(1)=3+1-1 | | -x-3(0.5)=3 | | y=ln(x+3)+ln(5) | | 4x^2-9y^2+4x+18y-68=0 | | 8d^2+28d+20=0 | | -3y+6-3y=3 | | -20m-12=80 |